Primary Prevention Knowledge of Parents and Teachers of Nursery and Play Group on Childhood Sexual Abuse - Nnenna Clara Okoroafor (International Journal of Evaluation and Research in Education (IJERE), 2012)
This research explored child sexual abuse (CSA), knowledge and prevention media among parents of pupils and teachers of nursery schools and playgroup. This research was conducted in qualitative mythology, through in-depth interviews (IDIs), and focus group discussions (FGD). In-depth interview held for 10 nursery school teachers and playgroup teachers. For children aged 0-5 years, FGD was conducted towards 10 parents of nursery School and 12 parents of playgroup. The study explored the following: parents’ and teachers’ knowledge on child sexual abuse prevention. The child sexual abuse prevention messages were provided to the children and topics they discussed and their attitudes towards child sexual abuse prevention education in school. The proposed primary prevention media strategies for parents were speech and posters as well as for nursery and playgroup teachers who understood the CSA impact. Research concluded that parents didn’t understand CSA concepts; media proposed for primary prevention are through dialogue and poster. Nursery, playgroup teachers and parents understood with poster media. Parents and teachers were encouraged to focus on the early prevention by building child sexual abuse knowledgeable community. DOI: http://dx.doi.org/10.11591/ijere.v1i2.1664